Lethal synergy between toxins of staphylococci and enterobacteria: implications for sudden infant death syndrome. - Sayers, N M (1995)
AIM--To test the hypothesis that lethal synergy occurs between toxin preparations of nasopharyngeal staphylococci and enterobacteria from sudden infant death syndrome (SIDS) victims and matched healthy infants. METHODS--SIDS and matched healthy babies were studied if both staphylococcal and enterobacterial strains were isolated from the nasopharynx. The lethality of toxin preparations from each bacterial isolate (separately and combined) was assessed over a range of dilutions using the chick embryo assay system. RESULTS--Staphylococci and enterobacteria were isolated together from the nasopharynx of seven SIDS babies but from only one normal healthy infant. Enterobacterial toxins were lethal at high dilutions. Staphylococcal toxins were less toxic. Simultaneous testing in the chick assay of staphylococcal and enterobacterial toxins, from each baby, at non-lethal concentrations enhanced lethality levels by 177 to 1011% compared with lethality expected by an additive effect alone. CONCLUSIONS--Synergy occurs between the toxins of nasopharyngeal staphylococci and enterobacteria. This combination of strains is more likely to occur in the nasopharynx of SIDS victims than that of healthy infants.